Information Literacy for Social Workers: University at Albany Libraries Prepare MSW Students for Research and Practice - Mary Jane Brustman; Deborah Bernnard (Communications in Information Literacy, 2008)
In a series of workshops, University at Albany librarians collaborate with the School of Social Welfare to impart information literacy skills to Master in Social Work students. The rationale, curriculum, and embedded ACRL information literacy standards are discussed. Also presented are assessments and a discussion of the challenges of implementation.